POTENSI KACANG HIJAU MENJADI BAHAN BAKU DALAM PEMBUATAN TEMPE SEBAGAI SUMBER BELAJAR PADA MATERI BIOTEKNOLOGI KONVENSIONAL - Siti Wardatul Jannah (Sekolah Tinggi Pariwisata Mataram, 2022)
In education, at least it must include how to measure ability, mastery of knowledge, attitude of values ​​and responsibility in learning, so innovation and development that are more creative and contextual are needed to increase mastery of knowledge in learning materials. Conventional biotechnology material in the study of the potential of mung bean as a raw material for making tempeh is seen as an innovative step in increasing a more contextual understanding. This qualitative research with descriptive method aims to describe the results of research with sources of data and information from various credible and adequate literature